Media Promosi Jurusan Teknik Komputer dan Jaringan SMK Muhammadiyah Kudus Menggunakan Animasi 3 Dimensi - Herlambang, Faizal Arya; Listyorini, Tri; Supriyati, Endang (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2023)
One of the primary needs in an agency is the need for promotional media. This is because the promotional media determines how long a system will last at a particular institution. In the commercial sector, promotional media are often used. However, to entice students to study, promotions are needed in educational institutions. One of the SMKs in Kudus is Muhammadiyah Kudus Vocational School which often gets awards, especially in the Computer and Network Engineering major. The data collection methods used in this research are literature study, interviews, and observation. Multimedia Development Life Cycle (MDLC) is the methodology applied in this study. The output of this research is the creation of a 3-dimensional animated video for the Computer and Network Engineering department at Muhammadiyah Kudus Vocational School. With this 3-dimensional animated video, prospective students who will continue their vocational high school can easily get to know the Department of Computer and Network Engineering at Muhammadiyah Kudus Vocational School and can see a physical picture visualized in 3D.